Jewish identity in the Greco-Roman world = Jüdische identität in der griechisch-römischen welt - Frey, Jörg; Schwartz, Daniel R.; Gripentrog, Stephanie (Ancient Judaism and early Christianity ;, 2007)
"The articles discuss various aspects of Jewish identity in the Greco-Roman period. Was there a common 'Jewish' identity, and how could it be defined? How could different groups develop and maintain their identity within the challenge of Hellenistic and early Roman culture? What about the images of 'others'? How could some of those 'others' adopt a Jewish lifestyle or identity, whereas others, abandoned their inherited identity? Among the questions discussed are the translation of Ioudaios, Jewish and universal identity in Philo, the status of women and their conversion to Judaism, the participation of non-Jews in the temple cult, the practice of Emperor worship in Judaea, and the image of Egypt and the Nile as 'others' in Philo. Two articles enter the debate whether Jewish identity had an ongoing influence within early Christianity, in Paul and in the rules known as the Apostolic Decree."--Jacket